(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Emotions and education are closely related, since adequate emotional management is required to face academic challenges favorably. Socioemotional skills are personal resources for effectively managing personal and social change and coping with difficult emotions. The objective was to determine the influence of role-playing as a methodological strategy in the development of socio-emotional skills in university students. The study had a quantitative approach, applied type, with an experimental, quasi-experimental design. The sample consisted of 252 students from the Faculty of Health of a fifth-cycle private university. Information collection was carried out through the revised version of the social skills scale composed of six dimensions. The results showed that the role-playing program develops socioemotional skills due to U-MannWhitney =.000 and z= -13.725. It is concluded that the role-play strategy helps to address a tension-free environment, enhancing the personal and interpersonal skills of university students.